PEMBINAAN KARAKTER TEOPRENEUR PEMUDA DENGAN PENDEKATAN KONSTRUKTIVISME DI GEREJA SUNGAI YORDAN JEMAAT SHALOM - Telaumbanua, Arozatulo (PkM: Pistotites, 2024)
With increasing human needs in the technological age, it is very necessary to equip, form and teach church youth to be able to open businesses and utilize technology that provides income to meet the needs of youth and congregation. Apart from developing the theopreneur character of church youth, Nias culture is also one of the reasons behind the emergence of the idea to develop the character of youth theopreneur from an early age in preparing them to become Christian entrepreneurs who are able to help and support the church and God's congregation. The method used in this community service activity is the lecture, question and practice method carried out at the Sungai Jordan Church, Jemaat Shalom. Based on the results of community service activities, it was found that young people still do not understand how important it is to develop their entrepreneurial character, because in the youth's view, we are still young and do not have money as capital. Apart from that, young people testified that they have entrepreneurial potential, including the potential to open salons, taylors and broiler chicken businesses.